Over-Expression of OsHOX24 Confers Enhanced Susceptibility to Abiotic Stresses in Transgenic Rice via Modulating Stress-Responsive Gene Expression - Bhattacharjee, Annapurna; Sharma, Raghvendra; Jain, Mukesh (Frontiers in Plant Science, 2017)
Homeobox transcription factors play critical roles in plant development and abiotic stress responses. In the present study, we raised rice transgenics over-expressing stress-responsive OsHOX24 gene (rice HD-ZIP I sub-family member) and analyzed their response to various abiotic stresses at different stages of development. At the seed germination stage, rice transgenics over-expressing OsHOX24 exhibited enhanced sensitivity to abiotic stress conditions and abscisic acid as compared to wild-type. OsHOX24 over-expression rice seedlings showed reduced root and shoot growth under salinity and desiccation stress conditions. Various physiological and phenotypic assays confirmed higher susceptibility of rice transgenics towards abiotic stresses as compared to wild-type at mature and reproductive stages of rice development too. Global gene expression profiling revealed differential regulation of several genes in the transgenic plants under control and desiccation stress conditions. Many of these differentially expressed genes were found to be involved in transcriptional regulatory activities, besides carbohydrate, nucleic acid and lipid metabolic processes and response to abiotic stress and hormones. Taken together, our findings highlighted the role of OsHOX24 in regulation of abiotic stress responses via modulating the expression of stress-responsive genes in rice.